The impact of initial statin treatment decisions on cardiovascular outcomes in clinical care settings: estimates using the Archimedes Model - van Herick A; Schuetz CA; Alperin P; Bullano MF; Balu S; Gandhi S (Dove Medical Press, 2012)
Andrew van Herick,1 C Andy Schuetz,1 Peter Alperin,1 Michael Bullano,2 Sanjeev Balu,2 Sanjay Gandhi21Archimedes, Inc, San Francisco, CA, USA; 2AstraZeneca Pharmaceuticals LP, Wilmington, DE, USAPurpose: Many patients treated for dyslipidemia do not achieve recommended cholesterol goals despite the widespread availability of effective statins. Pharmaceutical claims show a strong tendency for patients to remain on their initially assigned treatment. With computer simulations, the impact of initial statin treatment decisions on medium- and long-term cardiovascular outcomes were examined.Patients and methods: Using the Archimedes Model, three treatment scenarios were simulated. Patients initiated treatment with simvastatin (20, 40, or 80 mg), atorvastatin (10, 20, 40, or 80 mg), or rosuvastatin (10, 20, or 40 mg), and periodically intensified treatment. The simulated population consisted of 50,025 patients, aged 45–70 years, with low-density lipoprotein cholesterol exceeding goal. The proportion of patients initiating each dose was calibrated to United States pharmacy claims. Patients not reaching goal intensified the dose of their current statin or switched to an appropriate dose of rosuvastatin at rates matching pharmacy claims. Biomarkers and major adverse cardiovascular events (MACE) were tracked for 10 years and several high-risk subpopulations were analyzed. Statin models used biomarker effects from the STELLAR (Statin Therapies for Elevated Lipid Levels Compared Across Doses to Rosuvastatin) trial and outcomes data from various trials.Results: Initiating therapy with rosuvastatin reduced MACE more than simvastatin or atorvastatin. The 5- year relative risk of MACE was 0.906 (95% confidence interval: 0.888–0.923; P < 0.001) for initial treatment with atorvastatin rather than simvastatin, 0.831 (0.812–0.850; P < 0.001) for rosuvastatin rather than simvastatin, and 0.918 (0.898–0.938; P < 0.001) for rosuvastatin rather than atorvastatin. Subgroups with higher MACE incidence experienced greater absolute benefit.Conclusion: Considering observed rates of treatment intensification, initial treatment choices appear to significantly impact medium- and long-term cardiovascular risk. Patients at high cardiovascular risk are good candidates for aggressive initial therapy.Keywords: rosuvastatin, atorvastatin, simvastatin, simulation, modeling